2006
DOI: 10.1177/153537020623100409
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking Cell Surface Chemokine Receptors Leads to Isolation, Activation, and Differentiation of Monocytes into Potent Dendritic Cells

Abstract: Monocytes express on the cell surface several kinds of chemokine receptors that facilitate chemotaxis followed by differentiation in target tissues. In the present study, we found that a large number of monocytes from peripheral blood mononuclear cells (PBMCs) tightly adhered to plastic cell culture plates precoated with a monoclonal antibody (mAb, clone T312) specific for human CCR5 but not an isotype control after overnight incubation. Soluble T312 did not induce such adhesion, indicating that cross-linking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Among these down-regulated genes, the chemokine receptor ccr3, which is highly expressed in immature dendritic cells, and reported to be repressed in inflammatory conditions was found to be down-regulated [40]. By contrast, the transcription of markers of DC maturation ( cd40 and cd83 ) was increased after stimulation and clearly showed that maturation has occurred, whereas genes involved in cell to cell signaling and cell adhesion ( sulf2 and cdh1 ) were repressed.…”
Section: Discussionmentioning
confidence: 93%
“…Among these down-regulated genes, the chemokine receptor ccr3, which is highly expressed in immature dendritic cells, and reported to be repressed in inflammatory conditions was found to be down-regulated [40]. By contrast, the transcription of markers of DC maturation ( cd40 and cd83 ) was increased after stimulation and clearly showed that maturation has occurred, whereas genes involved in cell to cell signaling and cell adhesion ( sulf2 and cdh1 ) were repressed.…”
Section: Discussionmentioning
confidence: 93%
“…MCF-7 breast cancer cell line (ATCC®) was cultivated in RPMI 1640 as reported [24]. Monocytes from PBMC were isolated from heparinized (5 U/ml) blood of ten healthy male donors (29.8 ± 7.4 years old) by a standard density gradient centrifugation at 400 g using lymphocyte separation medium (Sigma Chemical) for 15 minutes at room temperature as described [25]. The cells at the interface were collected and washed three times in cold PBS containing 0.1% BSA.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the Balb/c Rag2 −/− g c −/− HIS mouse was used to study human disease, particularly infection by HIV Gorantla et al 2006;Zhang et al 2006), opening the road to developing new therapeutic approaches. However, HIS mice also provide an in vivo tool allowing for a more in-depth analysis of human lymphocyte development by providing access to human lymphocytes from tissues that are typically difficult to obtain.…”
Section: Balb/c Rag2 −/− G C −/− His Micementioning
confidence: 99%
“…In addition, we recently found a simple method to isolate monocytes from bulk PBMC by using antichemokine receptor monoclonal antibody-coated plates (Nimura et al 2006). A conventional method for generating DC from monocytes has been established, and there are commercially available kits for monocyte purification.…”
Section: Intra-splenic Inoculation Of Hu T Cells and DCmentioning
confidence: 99%